solve the equation x + 6 = 4 ( 3 - x ) + 9
Answers
Answered by
1
Answer:
this is the way of solving sum which you gave,thank u
Attachments:
![](https://hi-static.z-dn.net/files/df7/fb8f918a90044739d7874dd71c7e3ef3.jpg)
Answered by
6
Step-by-step explanation:
x+6=4(3-x)+9
x+6=12-4x+9
=x+4x=12+9-6
=5x=21-6
=5x=15
x=15/5
x=3
verification
x+6=4(3-x)+9
3+6=4(3-3)+9
9=4×0+9
9=9
Similar questions
Science,
7 months ago
Computer Science,
7 months ago
Chemistry,
7 months ago
Computer Science,
1 year ago
Science,
1 year ago
Hindi,
1 year ago